Peran Personalisasi Layanan dan Komunikasi Pemasaran Digital Dalam Membentuk Retensi Pelanggan di Klinik Utama Cipta Ayu - Renancy Pratiwi; Endang Sulistya Rini; Doli Muhammad Jafar Dalimunthe (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The beauty clinic industry in Indonesia has seen significant growth, yet heightened competition demands that clinics retain customers through personalized services and effective digital marketing communication. Klinik Utama Cipta Ayu continues to encounter challenges, including limited service personalization, delayed digital responses, and irrelevant online content, all of which contribute to unstable customer retention rates. This study aims to assess the partial and simultaneous effects of digital marketing communications and service personalization on customer retention. The research employed an associative technique with a quantitative approach. A purposive sampling method was used to select a sample of 130 respondents. Data was collected through a Likert-scale questionnaire, and multiple linear regression analysis was applied. Reliability testing yielded a Cronbach’s Alpha of 0.904, demonstrating strong reliability, while validity tests confirmed that all items were valid. The findings indicate that customer retention is positively and significantly influenced by service personalization. Additionally, digital marketing communications also have a positive and significant impact on customer retention. Both factors collectively contribute substantially to retention. These results emphasize the importance of regular in-person interactions, rapid digital responses, and relevant communication content in fostering long-term customer relationships.